Calibração e avaliação de novas cultivares de arroz no modelo SimulArroz - Poersch, Anderson Haas (2021)
With the growing global concern regarding the lack of food, the rice culture should gain even more prominence in the coming decades. This scenario directly impacts efforts that must be made in this sector and the use of technologies becomes more relevant to this reality. In this line of new technologies there is SimulArroz, a mathematical model based on processes that simulates the growth, development and productivity of cultivars until then adapted to the southern region of Brazil. Thus, the objective is to calibrate and evaluate the SimulArroz model for two new rice cultivars. Experiments were carried out at the Regional Research Station of the Instituto Rio Grandense do Arroz in Cachoeirinha / RS, and data from the Value of Cultivation and Use (VCU) tests of the Brazilian Agricultural Research Corporation (EMBRAPA Clima Temperado) in Alegrete, Capão do Leão were used , Santa Vitória do Palmar and Uruguaiana in Rio Grande do Sul, in addition to experiments in the experimental area of EMBRAPA Arroz e Feijão in Goianira / GO, representing the tropical region of Brazil. Haun Stage (HS) evaluations were carried out for the cultivars BRS Pampa and BRS Catiana from the beginning of the crop development until the formation of the flag leaf and phenology evaluations according to the scale of Counce et al. (2000). Plant collections for the determination of dry matter were carried out in Cachoeirinha for a BRS Pampa and BRS Catiana cultivar and in Goianira for a BRS Catiana cultivar. The model was calibrated and evaluated to simulate in an acceptable way the number of leaves in the main stalk, the phenology and accumulation of total dry matter of the aerial part of leaves, stalks and grains, and also for the productivity of cultivars in the tropical region of Brazil, enabling apply the model in the tropical region of irrigated rice production.